The Climate Change Impact on Drought Characteristics in North Lombok Regency - Humairo Saidah; Lilik Hanifah; I Dewa Gede Jaya Negara (Jurnal Penelitian Pendidikan IPA, 2023)
Lombok Island is part of Indonesia which has a high vulnerability to drought. The area that often experienced drought severely on Lombok Island is North Lombok Regency. This study wants to examine the effect of climate change on drought characteristics in this region using the standardized precipitation index method using four rain stations in the North Lombok region rainfall recording data of 20 years (1999-2018). The analyses were taken into two groups of a 10-year time scale, 1999-2008 and 2009-2018, to overview both of the 10-years drought characteristics. Drought index values ​​were observed on a period of 1-month (SPI1), 3-months (SPI3), and 6-months (SPI6) to get the map of drought duration, drought magnitude, drought intensity, and relative frequency. The results show that the drought characteristics in Lombok showed a decrease significantly in all measurement parameters used. The SPI3 results have shown the drought duration was decreasing in the last 10 years by 87%, from 2,43 to 0.03 months. The strength of the drought decreased by 88%, from -1.03 to 0.12 (severely dry to normal). Then the drought intensity became lower up to 87% from -0.22 to -0.03 monthly, and the relative frequency of drought events decreased by 83%. Signs of the decline were further followed by the same decreasing trends in the 6-month drought index, SPI6. The decrease in the drought parameter index illustrates that climate change impact has reduced the risk of drought disaster on the island of Lombok in the future